Genuine dissaving and optimal growth - Simone Valente (ETH Zurich, CER-ETH - Center of Economic Research, 2005)
Green accounting theories have shown that negative genuine savings at some point in time imply unsustainability. Consequently, recent studies advocate the use of the genuine savings measure for empirical testing: a negative index implies sustainability be rejected. This criterion is not forward-looking: positive current genuine savings do not rule out 'genuine dissaving' in the future. This paper derives a one-to-one relationship between the sign of longrun genuine savings and the limiting sustainability condition in the capital-resource model: if the sum of the rates of resource regeneration and augmentation exceeds (falls short of) the discount rate, long-run genuine savings are positive (negative). Testing this limiting condition allows to reveal whether current genuine savings are delivering a false message.
Keywords: Q01; O47; D90; 330; Genuine Saving; Green Accounting; Renewable Resources; Sustainable Development; Technological Progress; Umweltbericht; Erneuerbare Energie; Nachhaltige Entwicklung; Technischer Fortschritt; Intertemporale Allokation